The Relationship Of The Role Of Parents In Providing Reproductive Health Education And Care Of Genital Organ Hygiene In Adolescent Women In Man Model Manado - Anggun Sasmita; Umratun Hayati; Cristina Tien Popang; Anisa Nanang Sulistiyowati (Jurnal Ilmiah Kedokteran dan Kesehatan, 2024)
Genital hygiene care is to prevent and control infection, prevent skin damage, increase comfort, and maintain personal hygiene. The low knowledge of adolescents regarding aspects of reproductive health in adolescents is caused by the information they obtain mostly not coming from experts in the field, but instead from information sources that are sometimes even misleading. This research aims to determine the relationship between the role of parents in providing reproductive health education and genital hygiene care for young women in MAN Model Manado. This research uses an analytical survey with a cross sectional study design. Sampling using proportionate random sampling technique was 73 people. The conclusion of this research is that the majority of respondents' parents have a poor role in caring for the cleanliness of genital organs in adolescent girls, amounting to 47 people (64.4%) and at least the parents of respondents have a good role in caring for the cleanliness of genital organs in adolescent girls. as many as 26 people (35.6%). There is a relationship between the role of parents in providing reproductive health education with genital hygiene care for adolescent girls at MAN Model Manado. With the results of the chi-square statistical test analysis, a significance level of 0.000 was obtained. Further research is needed regarding reproductive health in adolescent girls.